A Wheat Allene Oxide Cyclase Gene Enhances Salinity Tolerance via Jasmonate Signaling . Issue 2 (10th December 2013) - Zhao, Yang; Dong, Wei; Zhang, Naibo; Ai, Xinghui; Wang, Mengcheng; Huang, Zhigang; Xiao, Langtao; Xia, Guangmin
Abstract : A jasmonic acid biosynthesis enzyme enhances wheat salinity tolerance . Abstract: One of the two branches of the α-linolenic acid metabolism pathway is catalyzed by 12-oxo-phytodienoic acid reductase I, and the other is involved in jasmonic acid (JA ) synthesis. The former is known to be active in the response to salinity tolerance in wheat ( Triticum aestivum ), but the participation of the latter in this response has not been established as yet. Here, the salinity-responsive bread wheat gene TaAOC1, which encodes an allene oxide cyclase involved in the α-linolenic acid metabolism pathway, was constitutively expressed in both bread wheat and Arabidopsis ( Arabidopsis thaliana ). In both species, transgenic lines exhibited an enhanced level of tolerance to salinity. The transgenic plants accumulated a higher content of JA and developed shorter roots. Both the shortened roots and the salinity tolerance were abolished in a background lacking a functional AtMYC2, a key component of the JA and abscisic acid signaling pathway, but were still expressed in a background deficient with respect to abscisic acid synthesis. We provide the first evidence, to our knowledge, suggesting that JA is also involved in the plant salinity response and that the α-linolenic acid metabolism pathway has a regulatory role over this response.